ANALISIS PENGARUH KUALITAS PRODUK YANG DIPERSEPSIKAN DAN MEREK ISLAM TERHADAP KEPERCAYAAN PRODUK HALAL (STUDI KASUS MAHASISWA AKADEMI FARMASI YARSI PONTIANAK) - Suryaningrat, Dani (Jurnal Ekonomi Integra, 2025)
Countries that are predominantly Muslim, halal products whether branded Islamic or not are an option for consumers. Consumers believe that Islamic brands and labeled products provide peace and security in using them. Research has been conducted with the title Analysis of the effect of perceived product quality and Islamic branding on trust. The research objective is to measure the influence of perceived product quality variables and Islamic branding on trust. This study uses a quantitative approach using a descriptive causality method by describing the conditions as they are based on data obtained during research on students of the Yarsi Pontianak Academy of Pharmacy as many as 120 respondents. This aims to process data quickly and precisely. Based on the formulation of the problem and the results of data analysis that has been carried out on the effect of perceived product quality and Islamic branding on trust (case study on Akfar Yarsi Pontianak students), it can be concluded that the results of this study show that perceived product quality and Islamic branding simultaneously have an influence of 38.3% on trust in halal products.